Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) Terhadap Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMPN 4 Pariaman - ISABELA . (Jurnal Edukasi dan Penelitian Matematika, 2019)
understanding0of mathematical concepts is a basic ability that must be possesed by student, but understanding the mathematical concepts of student in class VIII SMPN 40Pariaman is still low in terms oftest results and learning is still centered on education. The solution applied in the cooperatif learning model is think talk write0type. The purpose of this study is to describe the ability to understand0mathematical concept of student learning with the TTW model and how the development of studen’s understanding ability concept after the TTW model is applied. This type of research0is quasy experiment and describtive with randomized only0control group desig. The results of the analysis concluded the ability to understand mathematical concepts of students0increased0and quizzes for each meeting fluctuated. Keywords– Think Talk Write (TTW), Matematics concepts0understanding